Discourses about national history in Chilean cinema of fiction - Santa Cruz A., Eduardo (Re-presentaciones: Periodismo, comunicación y sociedad, 2018)
Chilean cinema of fiction has had national history as one of its themes. In relation to various economic contexts, political, ideological and cultural, films have been produced that have referred to historical characters, male or female; to specific historical events or, finally, that have been set in the past. An important part of the national production has had a focus on the discourse of national identity that has been called nacionalista-conservador, which proposes the existence of a “Chilean identity” which due to its ahistorical essence, lies beyond the differences and conflicts and remains unchanged in its basic features. The text tries to establish its connection with feature films produced in our country in different contexts. The analysis used the categorization referred to above, both to select films, as to relate the contents of the above-mentioned discursivity. Methodologically, this is central to the socio-cultural approach to the0 research, focused more on the joints than in the immanences of the texts.
Keywords: Chilean cinema; historical discourse; national identity